Carbon neutralization frontier tracking - Shi, Xiaoliang; Xin, Jiayin; Aria, Aruna; Lu, Ji; Wang, Tielong; Xu, Xiaowei; Zhang, Yiwen (Frontiers in Environmental Science, 2024)
Global warming causes sea level rise, frequent extreme weather, and other problems that the world's governments and people attach great importance to. Carbon neutrality has charted the course for a green and low-carbon transition and injected new momentum into global climate governance. Carbon neutrality has become one of the main measures taken by governments, businesses, and individuals around the world to combat global warming. Exploring the current international research status and development frontier in the field of carbon neutrality can not only provide a theoretical reference for the follow-up research on carbon neutrality but also provide useful ideas for the policy formulation of carbon neutrality in various countries. Using the SCI-E and SSCI databases of the "Web of Science Core Collection" as sample data sources, this study systematically analyzed 2223 papers in the field of international carbon neutrality research by using CiteSpace visual measurement software in order to track the trend and influence of countries, scientific research